Comparison studies on phase formation and transformation behavior between Ni-Ti and Ni-TiH2 synthesized via solid state sintering - Mohd Zaki, Hafizah Hanim; Mohamad Sholihin, Mohamad Hanis; Abdullah, Jamaluddin; Sarifuddin, Norshahida (UR-Publishers, 2018)
Solid state synthesis is an alternative processing technique that has been attempted for producing novel-structured NiTi such as porous NiTi and other novel forms. Whilst shape memory effect is a unique advantage of NiTi shape memory alloy like, no successful attempt so far to produce single phase NiTi with good martensitic transformation behavior. As oxidation of Ti is the main problem that may retard the formation of single phase NiTi, the preliminary study of the effect of powder precursor was done. In this research, a systematic comparative investigation was performed on phase formation and transformation behavior of Ni-Ti and Ni-TiH2 sintered specimen. It revealed that no martensitic transformation was observed for Ni-Ti specimen, attributed to minor NiTi phase formation. In addition, the XRD result of powder analysis indicates that part of Ti powder was oxidized during specimen preparation which creates imbalance composition for Ni-Ti reaction. In contrast, Ni-TiH2 specimen displayed martensitic transformation behaviour attributed to high amount of NiTi phase formation. This reflects that the use of TiH2 to replace Ti as powder precursor has a significant effect towards NiTi phase formation and its transformation behaviour.